Day type and start time may influence sleep in adolescent professional football players - Edinborough, L.; Bruce-Low, S.; Hill, J.; Woodhouse, J.; Jarvis, M.; Pedlar, C. (International Journal of Sports Medicine, 2023)
This study assessed whether scheduling (start time and day type) and workload variables influenced sleep markers (activity monitor) in professional academy footballers (n=11; 17.3±0.7 yrs) over a 10-week in-season period. Separate linear mixed regressions were used to describe the effect of start time on the previous nights sleep, and the effect of day type (match day, match day+1) and workload on subsequent sleep. Workload variables were modelled by day (day), 7-day (acute), and 28-day (chronic) periods. Sleep duration following match day+1 (400 mins; 95%CI:368-432) was significantly reduced compared to all other day types (p<0.001). Sleep onset time following match day (00:35; CI:00:04-01:12) and wake time on match day+1 (09:00; CI:08:37-09:23) were also significantly later compared to all other day types (p<0.001). Sleep duration (19.1 mins; CI:9.4-28.79), wake time (18 mins; CI:9.3-26.6), and time in bed (16.8 mins; CI:2.0-31.5) were significantly increased per hour delay in start time. When no activity was scheduled, sleep duration (37 mins; CI:18.1-55.9), sleep onset (42.1 mins; CI:28.8-56.2), and wake times (86 mins; CI:72-100) were significantly extended, relative to a 09:00 start time. Day, acute, and chronic workloads were associated with sleep onset and wake times only. Scheduled start times were associated with changes in sleep duration. Therefore, delaying start times may increase sleep in this population.